FRI0226 Tocilizumab Is Similarly Effective in RA Patients with No or Up To Two Prior Bdmard Failures: Results from The German Prospective Cohort Study Rabbit. (15th July 2016) - Baganz, L.; Strangfeld, A.; Kekow, J.; Bussmann, A.; Krause, A.; Stille, C.; Listing, J.; Richter, A.; Zink, A.
Abstract : Background: In Germany, Tocilizumab (TCZ) is used for the treatment of rheumatoid arthritis both in biologic-naïve patients and those with previous failures of biologic (b)DMARDs. Objectives: To investigate effectiveness and retention rates of TCZ in patients with multiple bDMARD failures. Methods: We included 885 RA patients enrolled with the start of TCZ treatment between 2009 and 2015 in the German biologics register RABBIT (R heumatoid a rthritis: Ob servation of b iologic t herapy). Patients were stratified according to the number of bDMARD failures prior to the initiation of TCZ: biologic naive (n=318), 1 bDMARD failure (n=286), 2 bDMARD failures (n=186), ≥3 bDMARD failures (n=95). We used Kaplan-Meier survival methods to examine the retention rates within 12 months after the initiation. Discontinuation was defined as stopping TCZ therapy. Effectiveness regarding the control of disease activity (mean DAS28-ESR) over 3, 6 and 12 months was examined with linear mixed models. Results: Compared to biologic naive patients those with prior bDMARD failures at start of TCZ were younger but had significantly longer disease duration (bio-naive: 8, 1 bDMARD failure: 11.6, 2 failures: 13.3 and ≥3 failures: 15.3 years; p<0.01). The DAS28 at baseline and loss of physical function were significantly higher in patients with ≥3 bDMARD failures. In the latter group patients with more than 2 comorbidities were also more frequent (21% (bio-naive), 31% (1), 24% (2), 38% (≥3 failures)). No differences were found regarding concomitant use of glucocorticoids and csDMARDs. All patients with ≥3 bDMARD failures had been exposed to TNF-inhibitors (TNFi), 60% had also been exposed to other bDMARD classes. In contrast, only 5.9% (12.9%) of patients with 1 (2) bDMARD failures had been exposed to non-TNFi. During follow-up in RABBIT, patients with ≤2 bDMARD failures reached low disease activity (DAS28) on average while those with ≥3 bDMARD failures remained in moderate disease activity. Treatment continuation on TCZ therapy was similar in biologic naive patients and in those with ≤2 bDMARD failures. Patients with ≥3 bDMARD failures had significantly lower continuation rates (Figure ). Adverse events (AEs) were the most frequent reason for discontinuation in all strata; in patients with ≥3 bDMARD failures the withdrawal of TCZ due to AEs occurred in 52% of patients. Conclusions: TCZ was similarly effective in biologic naive patients and in patients with up to 2 prior TNFi failures. The majority of those patients achieved low disease activity (DAS28<3.2). However, in patients with ≥3 bDMARD failures disease activity remained on a higher level and treatment continuity was significantly lower. It seems that despite all progress in the treatment of RA during the last decades a small patient group remains in which the disease is difficult to be controlled despite effective treatment. Disclosure: Supported by a joint, unconditional grant from AbbVie, Celltrion, Hospira, Bristol-Myers Squibb, MSD Sharp&Dohme, Pfizer, Roche, and UCB. Disclosure of Interest: None declared